2010
DOI: 10.1016/j.bbabio.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Probing binding determinants in center P of the cytochrome bc1 complex using novel hydroxy-naphthoquinones

Abstract: Atovaquone is a substituted 2-hydroxy-naphthoquinone used therapeutically against Plasmodium falciparum (malaria) and Pneumocystis pathogens. It acts by inhibiting the cytochrome bc1 complex via interactions with the Rieske iron-sulfur protein and cytochrome b in the ubiquinol oxidation pocket. As the targeted pathogens have developed resistance to this drug there is an urgent need for new alternatives. To better understand the determinants of inhibitor binding in the ubiquinol oxidation pocket of the bc1 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…They act between cytochromes b and c 1 of the bc1 complex [62][63][64][65][66]. Therapeutical naphthoquinones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They act between cytochromes b and c 1 of the bc1 complex [62][63][64][65][66]. Therapeutical naphthoquinones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1B), featuring a metabolically stable trifluoromethyl function and amethyl substituted aromatic ring (Fig. 1C and Refs 12, 13). The racemic mixture of R- and S-10576 had first been tested by Fieser and coworkers as an anti-malarial [14], who showed that although it was effective against avian malaria, it was ineffective in humans.…”
Section: Introductionmentioning
confidence: 99%
“…To improve drug bioavailability, several atovaquone analogs were prepared and changes were made to the naphthoquinone moiety, especially the alkyl side chain, because it is known that modifying this chain can alter drug activity [7] and counteract drug resistance [11-13]. Recently, it was demonstrated that 2-methyl-heptyl or 2-methyl-heptyl-trifluoromethyl 2-hydroxy-1,4-naphthoquinones were highly effective against atova-quone-resistant P. falciparum [14]. …”
Section: Introductionmentioning
confidence: 99%